Apex predators : the world's deadliest hunters, past and present - Jenkins, Steve, 1952- (Houghton Mifflin Harcourt, 2017)
"In his latest illustrated exploration of the animal kingdom, Steve Jenkins introduces readers to some of the most powerful predators in history, from the Tyrannosaurus rex to the African lion."--